2022
DOI: 10.1097/phh.0000000000001614
|View full text |Cite
|
Sign up to set email alerts
|

Staffing Up and Sustaining the Public Health Workforce

Abstract: Objectives: Estimate the number of full-time equivalents (FTEs) needed to fully implement Foundational Public Health Services (FPHS) at the state and local levels in the United States. Methods: Current and full implementation cost estimation data from 168 local health departments (LHDs), as well as data from the Association of State and Territorial Health Officials and the National Association of County and City Health Officials, were utilized to estimate current and "full implementation" staffing modes to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
(34 reference statements)
2
18
0
Order By: Relevance
“…When considering whether to implement communitybased mental health promotion and prevention (MHPP) programs, cost estimation is essential for determining program affordability and advocating for program funding [1][2][3][4][5]. Stakeholder-driven, community-based MHPP programs are posited to provide cost-effectiveness [6].…”
Section: Introductionmentioning
confidence: 99%
“…When considering whether to implement communitybased mental health promotion and prevention (MHPP) programs, cost estimation is essential for determining program affordability and advocating for program funding [1][2][3][4][5]. Stakeholder-driven, community-based MHPP programs are posited to provide cost-effectiveness [6].…”
Section: Introductionmentioning
confidence: 99%
“…Given earlier findings that showed that most Ohio LHDs did not have enough staff to fully provide the FPHS in their communities, 10 these findings are in line with prior work that has shown that LHDs likely needed to reassign staff from other FPHS areas to support their pandemic response. 7,8 In addition to reassigning staff internally, many LHDs also hired additional temporary staff. In Ohio, the median number of temporary staff hired was 9 in FY 2020 and 10 in FY 2021.…”
Section: Discussionmentioning
confidence: 99%
“…5 Even before the COVID-19 pandemic, state and local public health agencies lacked 80 000 full-time equivalent (FTE) staff to ensure full delivery of the Foundational Public Health Services (FPHS) in communities across the country. 6,7 As the pandemic unfolded, inadequate funding and limited staffing challenged public health agencies' capacity to respond to rapidly changing priorities. As a result, many agencies had to assign staff from other areas of public health practice to pandemic response.…”
mentioning
confidence: 99%
“…These recommendations could contribute to not only educating the population in basic public health principles but also help to alleviate the public health workforce shortage by introducing young adults to the field of public health. It is estimated that in the post-COVID-19 era, the local and state governmental public health workforce in the U.S. requires 80,000 full-time employees to deliver foundational public health services ( 19 ).…”
Section: Discussionmentioning
confidence: 99%